KARAKTERISTIK ORGANISASI, KOMPETENSI DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH KABUPATEN BURU SELATAN - MOHAMAD ARSAD RAHAWARIN (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to influence organizational characteristics, competence and disciplineon employee performance. This type of research is a descriptive and associative approach.Based on this opinion, the population in this study were all 86 of employees of Bappeda SouthBuru Regency. Determination of the number of samples is based on a sample table developedby Issac and Michael, where if a population of 86 people, then at a 5% confidence level, thenumber of samples is determined as much as 79. Data were analyzed by SEM LISREL. Theresults showed that (1) organizational characteristics had a positive and significant effect onemployee performance as seen from the path coefficient that was positive at 0.37 with a t valueof 2.25> 1.96. The biggest factor load value for organizational characteristics variable isresources, (2) competence has a positive and significant effect on employee performance asseen from the path coefficient that is positive at 0.60 with a t value of 2.32> 1.96. The variablesthat contribute to the formation of competency latent variables are self-concept with a factorload of 0.68, meaning that to improve employee competence, it is necessary to improve theawareness of self-concept, (3) discipline has a positive and significant effect on employeeperformance as seen from path coefficient which is positive is 0.47 with a value of t value 2.67>1.96. The variables that contribute to the formation of disciplinary latent variables arecompliance by 0.67, which means that employee discipline can be seen from the level ofcompliance with regulations and to superiors.